2018
DOI: 10.1111/pce.13371
|View full text |Cite
|
Sign up to set email alerts
|

Abscisic acid catabolism enhances dormancy release of grapevine buds

Abstract: The molecular mechanism regulating dormancy release in grapevine buds is as yet unclear. It was formerly proposed that dormancy is maintained by abscisic acid (ABA)-mediated repression of bud-meristem activity and that removal of this repression triggers dormancy release. It was also proposed that such removal of repression may be achieved via natural or artificial up-regulation of VvA8H-CYP707A4, which encodes ABA 8'-hydroxylase, and is the most highly expressed paralog in grapevine buds. The current study fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 71 publications
6
50
0
Order By: Relevance
“…In plants, abscisic acid (ABA) plays a crucial role in regulating bud dormancy including its induction, maintenance and release (Lenton, Perry, & Saunders, ; Zheng et al, , ). ABA also plays an important role in host–pathogen interactions (Mohr & Cahill, ; Qi et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In plants, abscisic acid (ABA) plays a crucial role in regulating bud dormancy including its induction, maintenance and release (Lenton, Perry, & Saunders, ; Zheng et al, , ). ABA also plays an important role in host–pathogen interactions (Mohr & Cahill, ; Qi et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Pear and apple dormancy is induced by low temperatures rather than the photoperiod (Heide and Prestrud ), whereas in poplar, short‐day conditions induce dormancy (Olsen et al, ). Although the environmental cues for establishing dormancy vary among species, ABA is considered to be the key phytohormone for dormancy induction and maintenance (Li, Xu, et al, ; Tylewicz et al, ; Zheng, Acheampong, Shi, Mugzech, et al, ). In poplar, ABA signaling promotes plasmodesmata closure, which is a crucial process during dormancy in response to short‐day conditions (Tylewicz et al, ), and helps regulate the onset of bud dormancy.…”
Section: Discussionmentioning
confidence: 99%
“…However, a long‐term exposure to low temperatures leads to endo‐dormancy release and a decrease in the ABA content of buds, likely due to the downregulated expression of ABA biosynthesis genes ( XERICO and NECD ) and the upregulated expression of an ABA catabolism gene ( CYP707A ) (Li et al, ; Zheng et al, ). The overexpression of VvCYP707A4 in grape decreases the ABA level and significantly enhances bud break (Zheng et al, ). Thus, ABA is involved in dormancy maintenance.…”
Section: Introductionmentioning
confidence: 99%
“…Our results suggested that the primary perception and signal cascade to initiate bud burst arises within the bud and are independent of de novo transport of phytohormones or other mobile elements from the cane. In fact, very recently, the induction of in situ catabolism of ABA was demonstrated to be essential for bud break in grapevine (Zheng et al , 2018). Moreover, the authors showed that the transgenic expression of the ABA catabolic enzyme VvA8H-CYP707A4 resulted in enhancement of bud break in grapevine, and reduced apical dominance (Zheng et al , 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, very recently, the induction of in situ catabolism of ABA was demonstrated to be essential for bud break in grapevine (Zheng et al , 2018). Moreover, the authors showed that the transgenic expression of the ABA catabolic enzyme VvA8H-CYP707A4 resulted in enhancement of bud break in grapevine, and reduced apical dominance (Zheng et al , 2018). Also recently, a transcriptomic study on Prunus mume suggested that low temperature results in the up-regulation of C-repeat binding factor genes, which directly promotes six dormancy associated MADS-box genes to establish dormancy.…”
Section: Discussionmentioning
confidence: 99%